KTSP TRANSITION TOWARDS 2013 CURRICULUM AT JUNIOR HIGH SCHOOL OF TAMAN DEWASA IBU PAWIYATAN TAMANSISWA, YOGYAKARTA - Husna US, Atik Nidaul; Wijayanti, Wiwik (EARR (Educational Administration Research and Review), 2020)
All of schools policy will surely reap different reactions. 2013 curriculum which was allegedly reformer of KTSP is now a big question about the success of its implementation. This study aims to describe the process of implementing the curriculum 2013 transition at Junior High School of Taman Dewasa Ibu Pawiyatan Tamansiswa, Yogyakarta. The method of this study was qualitative with the type of case study approach. The results of this study indicate that (1). Curriculum planning involves all relevant stakeholders, including: the principal, deputy head of curriculum, deputy head of students’ affairs, deputy head of facilities and infrastructure, teacher teams and school committees. (2). The implementation of the curriculum was carried out in stages. Starting with applying the 2 013 curriculum in grades 7 and 8, meanwhile grade 9 still uses the KTSP. (3). Evaluation of curriculum has two categories of assessment that come from internal and external schools.  The results describe that 2013 curriculum can be implemented gradually well. The conclusion is transition from KTSP to 2013 curriculum gradually. In the near future, the school will implement the 2013 curriculum thoroughly in every class without leaving the school’s specificity with the values of art, culture and character.